Wood pellet market and trade: a global perspective. (17th January 2013) - Goh, Chun Sheng; Junginger, Martin; Cocchi, Maurizio; Marchal, Didier; Thrän, Daniela; Hennig, Christiane; Heinimö, Jussi; Nikolaisen, Lars; Schouwenberg, Peter‐Paul; Bradley, Douglas; Hess, Richard; Jacobson, Jacob; et al.
Abstract: This perspective provides an overview of wood pellet markets in a number of countries of high significance, together with an inventory of market factors and relevant past or existing policies. In 2010, the estimated global wood pellet production and consumption were close to 14.3 Mt (million metric tonnes) and 13.5 Mt, respectively, while the global installed production capacity had reached over 28 Mt. Two types of pellets are mainly traded (i) for residential heating and (ii) for large‐scale district heating or co‐firing installations. The EU was the primary market, responsible for nearly 61% and 85% of global production and consumption, respectively in 2010. EU markets were divided according to end use: (i) residential and district heating, (ii) power plants driven market, (iii) mixed market, and (iv) export‐driven countries. North America basically serves as an exporter, but also with significant domestic consumption in USA. East Asia is predicted to become the second‐largest consumer after the EU in the near future. The development perspective in Latin America remains unclear. Five factors that determine the market characteristics are: (i) the existence of coal‐based power plants, (ii) the development of heating systems, (iii) feedstock availability, (iv) interactions with wood industry, and (v) logistics factor. Furthermore, intervention policies play a pivotal role in market development. The perspective of wood pellets industry was also analyzed from four major aspects: (i) supply potential, (ii) logistics issues, (iii) sustainability considerations, and (iv) technology development. © 2013 Society of Chemical Industry and John Wiley & Sons, Ltd